Transcriptome Profiling Based on Different Time Points After Hatching Provides a Core Set of Gene Resource for Understanding Larval Immune Response Mechanisms Against Vibrio anguillarum Infection in Amphioctopus fangsiao - Bao, Xiaokai; Li, Yan; Zhang, Jianbai; Chen, Xipan; Xu, Xiaohui; Feng, Yanwei; Sun, Guohua; Liu, Xiumei; Li, Bin; Wang, Weijun; Li, Zan; Yang, Jianmin (Frontiers in Marine Science, 2021)
Immune defense systems are indispensable for living organisms. Within an immune network, problems with any given link can impact the normal life activities of an organism. Amphioctopus fangsiao is a cephalopod that exists widely throughout the world’s oceans. Because of its nervous system and locomotive organs, it has become increasingly studied in recent years. Vibrio anguillarum is one of the most common pathogenic bacteria in aquaculture organisms. It is highly infectious and can infect almost all aquaculture organisms. V. anguillarum infection can cause many adverse biological phenomena, including tissue bleeding. Study the immune response after V. anguillarum infection would help us to understand the molecular mechanisms of immune response in aquaculture organisms. In this research, we infected the primary incubation A. fangsiao with V. anguillarum for 24 h. We analyzed gene expression in A. fangsiao larvae via transcriptome profiles at 0, 4, 12, and 24 h after hatching, and 1,385, 734, and 6,109 differentially expressed genes (DEGs) were identified at these three time points. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were used to identify immune-related DEGs. Protein–protein interaction networks were constructed to examine interactions between immune-related genes. Twenty hub genes involved in multiple KEGG signaling pathways or with multiple protein–protein interaction relationships were identified, and their differential expression verified by quantitative RT-PCR. We first studied V. anguillarum infection of A. fangsiao larvae by means of protein–protein interaction networks. The results provide valuable genetic resources for understanding immunity in molluscan larvae. These data serve as a theoretical basis for the artificial breeding of A. fangsiao.